Risk Management for Cash Waqf Institutions Based on Good Corporate Governance Perspective: Lessons Learned from an Islamic Rural Bank in Indonesia - Atina Rahmah Mawadah; Salman Abdurrubi Perwiragama; Abdul Mujib (Management of Zakat and Waqf Journal (MAZAWA), 2023)
Waqf, including cash waqf, is one of the Islamic social finance instruments that has been playing a significant role to develop community welfare throughout the history of Islam. Nowadays, Cash waqf significantly grows globally in countries like Saudi Arabia, Egypt, Kuwait, Turkey, Bangladesh, Malaysia, and Singapore. The unique feature of cash waqf is though it is subject to value volatility, shariah imposes that the value of cash waqf should not depreciate hence appreciation is required. Involving different parties in the process of cash waqf management, several risks may arise including moral hazards, conflict of interest, non-shariah compliance events, and so on. Thus, risk management becomes a must in managing cash waqf. Studies have deliberated on this issue and concluded with various findings. This study aims to use a Good Corporate Governance (GCG) perspective to examine risk management in the management of cash waqf at BPRS Barokah Dana Sejahtera. A qualitative method using semi-structured interviews was deployed to obtain primary data which has some extent of more comprehensive information to be analyzed rather than secondary data. This study concludes with some points including advantageous impacts on Cash Waqf Management Institution (LKS-PWU) regarding financial performance and the mauquf alaih nuance resulting from effective risk management. Moreover, the implementation of  GCG principles as a framework for risk management in Cash Waqf institutions encourages the community to continuously contribute to cash waqf through LKS-PWU.